Greene's protective groups in organic synthesis - Wuts, Peter G. M.; Greene, Theodora W. (Theodora Whatmough), 1931-2005.; Greene, Theodora W. (Theodora Whatmough), 1931-2005. (Hoboken, New Jersey : Wiley, 2014)
This new edition includes updates on protective group chemistry since 2005. Each chapter is updated to reflect the new material that has been published since the last edition, totalling over 2800 references. This continues the tradition of Greene's being comprehensive in the overall scope of coverage, providing the most relevant and useful examples to illustrate each methodology. It is a useful guide to the organic chemist, and the content is organized on the basis of the functional group to be protected (i.e., ethers, amides, phenols, phosphates, etc). Within each section, the organization goes from the simple protective groups to the most complicated (in terms of structure). --
Includes bibliographical references and index.
Text in English.
Print version record and CIP data provided by publisher.
Keywords: Organic compounds -- Synthesis; Protective groups (Chemistry); Protective groups (Chemistry); SCIENCE -- Chemistry -- Organic; Organic compounds -- Synthesis; Protective groups (Chemistry); Electronic books; Electronic books